Cytologic diagnosis of coccidioidomycosis: Spectrum of findings in Southern Arizona patients over a 10 year period. Issue 3 (22nd January 2016) - Aly, F. Zahra; Millius, Rebecca; Sobonya, Richard; Aboul‐Nasr, Khalid; Klein, Robert
Abstract : Background: The largest series examining the cytological diagnosis of coccidioidomycosis was reported more than 20 years ago and only considered fine needle aspiration (FNA) specimens from pulmonary nodules. Since then, there has been a substantial increase in the incidence of the disease in endemic regions. The aims of this study were to examine the spectrum of Coccidioides in all cytologic specimens and detail their diagnostic and clinical features. The prevalence of infection is also examined against temperature and precipitation data. Methods: The Department of Pathology database was retrospectively searched for cases diagnosed as coccidioidomycosis. Climate report was obtained from National Weather Service Forecast Office. Statistical analysis was carried out using JMP version 11.2.0. Results: The presence of Coccidiodes was microscopically diverse with immature spherules, variably sized spherules, endosporulating spherules, empty spherules, and ruptured spherules being observed. Bronchoalveolar lavages demonstrated the greatest number of different forms of Coccidioides and were associated with acute inflammatory response. Granulomas were rare and mostly seen in lymph nodes and extra pulmonary sites. A necrotic background with paucity of inflammation was frequently seen in lung FNA. Immune competent patients outnumbered immunocompromised patients, illustrating the importance of considering the diagnosis in all patients. The reported association between rainfall and peak prevalence was not observed in our study. Conclusion: Coccidioides has diverse cytological appearance and varied host response depending on the site and type of preparation examined. In endemic areas, the disease should be considered in all patients, independent of immune status, and throughout the year. Diagn. Cytopathol. 2016;44:195–200. © 2016 Wiley Periodicals, Inc.